Penerapan Internet of Things Berbasis Website pada Pengunci Pintu Otomatis - M. Fajar J. Kharisma; Danang Haryo Sulaksono; Gusti Eka Yuliastuti; Citra Nurina Prabiantissa; Nanang Fakhrur Rozi (Institut Teknologi Adhi Tama Surabaya, 2022)
Classroom is a main facility in teaching and learning activities. Safety and comfort are the main factors that are most considered, especially during the teaching and learning process. The problem faced is ensuring the safety of the classroom as long as the classroom is empty, so that it cannot be accessed by unauthorized students or lecturers. So far, classroom security only uses conventional lock doors, where this type of lock has several drawbacks, including locks that are easy to duplicate, locks are easy to break and locks are easily damaged. One solution to this problem is to design and build a web-based automatic lock door system. Internet of Things is a network concept that aims to extend the benefits of continuously connected connectivity. This study aims to design an alternative technology for house keys using a solenoid. Solenoid is an automatic lock sensor that can be controlled by Arduino Uno and works when given a voltage of 12V. The system testing carried out is calculated using QoS testing consisting of four parameters. First, the throughput value obtained is 54.024207 bytes/s which is classified into the Very Good Category for Classroom Security Systems. Second, the delay obtained an average value of 61.753323 ms which is classified into the Very Good Category for Classroom Security Systems. Third, the jitter value obtained is 7.8406 ms which is classified into the Very Good Category for Classroom Security Systems. Finally, packet loss obtained a value of 0% classified into the Very Good Category for Classroom Security Systems.